THE DEVELOPING METHODS OF STUDENTS’ PROFESSIONAL MOBILITY IN THE PROCESS OF LEARNING FOREIGN LANGUAGES - Nadirova Xilola, (TADQIQOTLAR, 2026)
Annotation Current examination of the student's readiness for professional mobility should be carried out based on the following set of methods: test; questionnaire; analysis of the results of self-study work and practical assignments, conducting control work.